Cataract extraction and intraocular pressure-lowering agents delivery: A nationwide French study between 2005 and 2017. Issue 4 (July 2022) - Chamard, Chloé; Huguet, Héléna; Bron, Alain M; Creuzot-Garcher, Catherine; Nogue, Erika; Villain, Max; Nagot, Nicolas; Carrière, Isabelle; Mura, Thibault; Daien, Vincent
Purpose: Cataract and glaucoma are among the leading causes of blindness worldwide in older people, and they are often concomitant. To assess topical intraocular (IOP)-lowering agents delivery changes after cataract extraction. Material and methods: Longitudinal matched exposed–unexposed study from the French national healthcare database from January 1, 2005 to January 1, 2017. We compared individuals using topical IOP-lowering agents who underwent bilateral cataract extraction with individuals matched on IOP-lowering agents load, age, and sex who did not undergo cataract extraction. IOP-lowering agents number of drops was assessed 12 months before the first cataract extraction and compared with number of drops 12 months after the second cataract extraction. Results: About 1194 individuals treated with IOP-lowering agents were included, 597 exposed to bilateral cataract extraction and 597 unexposed to any surgery (total mean age 74.8 ± 8.3 years; 69.0% women). Mean IOP-lowering agents delivery at baseline was 1.4 daily drops in both groups. The mean number of drops decreased greater in the exposed than unexposed group (−25.5% vs −3.5%; p < 0.0001). Overall, 159 (26.6%) and 48 (8.0%) individuals in the exposed and unexposed groups interrupted medication ( p < 0.0001). Conclusions: A decrease of around one quarter of IOP-lowering agents delivery was observed after cataract extraction in the present real-life study with a longstanding interruption observed in one quarter of patients. Phacoemulsification as a standalone procedure reduces IOP-lowering agents delivery in ocular hypertension and glaucoma.